2003
DOI: 10.1074/jbc.m300281200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of FGFRL1, a Novel Fibroblast Growth Factor (FGF) Receptor Preferentially Expressed in Skeletal Tissues

Abstract: Clones for a novel transmembrane receptor termed FGFRL1 were isolated from a subtracted, cartilage-specific cDNA library prepared from chicken sterna. Homologous sequences were identified in other vertebrates, including man, mouse, rat and fish, but not in invertebrates such as Caenorhabditis elegans and Drosophila. FGFRL1 was expressed preferentially in skeletal tissues as demonstrated by Northern blotting and in situ hybridization. Small amounts of the FGFRL1 mRNA were also detected in other tissues such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 24 publications
(44 reference statements)
3
87
1
2
Order By: Relevance
“…has been postulated to act as a decoy receptor due to ligand binding ability and the absence of a C-terminal tyrosine kinase domain (11,12,32). To explore the effect of FGFRL1 on beta-cell MAPK signaling activity, we examined ERK1/2 phosphorylation in ␤TC3 cells stably expressing the full-length (RL1) and truncated (RL1-⌬His and RL1-⌬C) receptor constructs (Fig.…”
Section: Terminus Of Fgfrl1 Enhances Mek/mapk Pathway Activation Inmentioning
confidence: 99%
See 1 more Smart Citation
“…has been postulated to act as a decoy receptor due to ligand binding ability and the absence of a C-terminal tyrosine kinase domain (11,12,32). To explore the effect of FGFRL1 on beta-cell MAPK signaling activity, we examined ERK1/2 phosphorylation in ␤TC3 cells stably expressing the full-length (RL1) and truncated (RL1-⌬His and RL1-⌬C) receptor constructs (Fig.…”
Section: Terminus Of Fgfrl1 Enhances Mek/mapk Pathway Activation Inmentioning
confidence: 99%
“…FGFLR1 Associates with Insulin Secretory Granules and Late Endosomes-Previous work has revealed that FGFRL1 localizes to secretory granules in HEK293 cells, a kidney cell line (31,32). To determine FGFRL1 localization in ␤TC3 cells, we co-expressed the full-length (RL1) and truncated (RL1-⌬His and RL1-⌬C) constructs with Phogrin eGFP , a marker for insulin secretory granules, and Rab7 eGFP , a marker for late recycling endosomes (Fig.…”
Section: Fgfrl1 Is Endogenously Expressed In Pancreatic Islets Andmentioning
confidence: 99%
“…11,12 The FGFRL1 gene shows particularly pronounced expression in the primordia of bones (eg, the maxillae, the mandibles, the ribs and the nose) and in the permanently cartilaginous tissues of the trachea. Although the muscle of the tongue and the diaphragm express FGFRL1 at a relatively high level, the heart, skeletal muscle, brain, lung, liver, kidney and gut express FGFRL1 at a basal level.…”
mentioning
confidence: 99%
“…Ген Fgf15 мыши имеет человеческий ортолог -ген FGF19, который кодирует белок FGF19, соответствующий Fgf15 мыши, поэтому их называют FGF15/19. В зависимости от функциональных свойств все факторы FGF делят на несколько подсемейств: паракринные (1-10, 16-20, 22); эндокринные, или гормоноподобные (15,19,21,23); и интракринные (11)(12)(13)(14). Секретируемые белки FGF способны индуцировать физиологический эффект в расположенных вблизи клетках-мишенях (паракринные FGF), а также оказывать системное влияние на отдалённые ткани и органы (эндокринные FGF).…”
Section: общая характеристика сигнального пути Fgf/fgfrunclassified
“…С недавнего времени выделяют FGFR5, или FGFRL1, сходный с другими FGFR по аминокислотной последовательности, но, по-видимому, не являющийся самостоятельным рецептором, поскольку он не имеет цитоплазматического тирозинкиназного домена, и передача сигнала происходит непрямым путём через FGFR1 [12][13][14] сигнальных путей: PLCg, STAT, FSR2-зависимых Ras/MAPK и PI3K/Akt (рис. 1а).…”
Section: общая характеристика сигнального пути Fgf/fgfrunclassified